Modulation of P2Y2 receptors in bovine cumulus oocyte complexes: effects on intracellular calcium, zona hardening and developmental competence - Fonseca, E. (Purinergic Signal, 2020)
The improvement of cryopreserved oocyte survival is imperative for the preservation of female fertility. In this study, we investigate whether P2Y2 receptors (P2Y2R) can be directly implicated in calcium (Ca(2+)) homeostasis misbalances observed during the cryopreservation process of cumulus oocyte complexes (COC). Firstly, RNA was extracted from bovine immature and mature oocytes and cumulus cells and real-time PCR performed to identify P2Y2R transcripts (experiment 1). Changes in intracellular calcium concentration [Ca2+]i of mature COC and oocytes (experiment 2) were measured upon exposure to cryoprotectants (CPA), UTP (P2Y2R stimulator, 100 μM), and/or suramin (P2Y2R inhibitor, 100 and 300 μM). The functional role of P2Y2R was investigated by analyzing the effect on oocyte viability of its modulation prior and during oocyte exposure to CPA (experiment 3). Mature COC were randomly divided into groups, and exposed to CPA and different P2Y2 modulators. Oocytes’ viability, cortical granules location, and competence for development were assessed. Results showed that P2Y2R mRNAs are expressed in both oocytes and cumulus cells. Stimulation with UTP and CPA led to [Ca2+]i increase, and this effect was totally or partially blocked by suramin (P2Y2R inhibitor). Oocyte exposure to CPA and UTP reduced embryo rates compared with control and suramin100μM (P ≤ 0.04). The observed enhanced premature zona hardening in oocytes exposed to CPA (P = 0.04) and UTP (P = 0.005) stimulus was inhibited by suramin 100 μM. In conclusion, inhibition of P2Y2R during cryoprotectant exposure reduces premature intracellular Ca(2+) release and significantly improves the developmental competence of exposed bovine oocytes.